Current Status of Vaccines Developed for SARS-CoV-2 Infection: A Review (Bangladesh Journal of Infectious Diseases, 2022)
COVID-19 is a respiratory disease caused by SARS-CoV-2 which at the beginning of 2020 started a global pandemic. During the pandemic, multiple medications have emerged to treat it, however, the best way to control this calamity is through the prevention giben y vaccines. This review has the aim of understanding the immune response triggered by SARS-CoV-2 and the strategies used by vaccines to fight it during the COVID-19 pandemic. The search was made in PubMed, Google Scholar, and Scopus using “SARS-CoV- 2”, “COVID-19”, “vaccines”, “immune response”, and “infection” as keywords, then 120 articles were selected. The challenge posed by SARS-Cov-2 infection has been addressed with the development of effective vaccines in a short time, additionally, some of them are innovative such as RNA vaccines. However, phase 3 trials indicate variations by population group that have had to be adjusted for the vaccine to be effective in different parts of the world. The current challenge is imposed by effective immunization against the variants that have emerged and are more contagious.Bangladesh Journal of Infectious Diseases, April 2022;9(Suppl_1): S40-S54